Anomalous right coronary artery in a middle-aged patient: A case report and review of the literature. Issue 49 (December 2016) - Rosseel, Liesbeth; Bonnier, Hans; Sonck, Jeroen
Abstract: Background: An anomalous right coronary artery originating from the left sinus of Valsalva is a rare, but often incidental, finding in middle-aged to elderly people. Prevalence is difficult to define, as well as determining potential harmful hemodynamic consequences. Moreover, the optimal treatment remains debatable. Case summary: The authors present a case of a middle-aged patient diagnosed with an anomalous right coronary artery causing ischemia, who was treated surgically. Conclusion: By reviewing literature, the authors conclude that choice of treatment depends on age, symptoms, and certain anatomic features of this anomaly. However, there are no randomized trials available in this field.